Thresholding and quantization algorithms for image compression techniques : a review - Lashari, Saima Anwar; Rosziati Ibrahim,; Nik Shahidah Afifi Md Taujuddin,; Norhalina Senan,; Suhaila Sari, (Penerbit Universiti Kebangsaan Malaysia, 2018)
With increasing demand on digital images, there is a need to compress the image to entertain the limited bandwidth and storage capacity. Recently, there is a growing interest among researchers focusing on compression of various types of images and data. Amongst various compression algorithms, transform-based compression is one of the promising algorithms. Despite the technological advances in transmission and storage, the demands placed on the bandwidth of communication and storage capacities by far outstrips its availability. This paper presents a review of image compression principle, compression techniques and various thresholding algorithms (pre-processing algorithms) and quantization algorithm (post-processing algorithms). This paper intends to give an overview to the relevant parties to choose the suitable image compression algorithms to suit with the need.